Corporate Social Responsibility(CSR) In Malaysia - Ontological And Epistemological Research Orientation In Building Theoretical Foundations - Nasruddin, Ellisha; Bustami, Mohammad Reevany (Universiti Sains Malaysia, 2012)
This research has studied CSR, through broad inclusiveness of stakeholders and dimensionality ofnitiatives/activities. The inclusiveness of stakeholders provides a framework for understanding the extent of corporate commitment towards socially responsible behaviour